STRATEGI KOMUNIKASI PEMASARAN PR AGENCY DALAM MENINGKATKAN EKSISTENSI SELAMA PANDEMI COVID-19 (STUDI KASUS MEDIA BUFFET PR) - Kiki Rizki Larasati (2022)
At the beginning of the COVID-19 pandemic, many industrial fields were affected, one of which was Media Buffet PR, which this year will only enter its 5th year. Media Buffet had to experience decreased activity and difficulty in getting new clients due to reduced mobility due to activity restriction regulations. All the activities that Media Buffet does, inevitably have to adapt online, not to mention the intense competition between PR agencies in Jakarta, making Media Buffet have to implement strategies to increase the company's existence. This study uses a qualitative method with a case study approach that focuses on Media Buffet PR's marketing communication strategy in increasing the company's existence. The informants of this study were 5 people who were selected with certain criteria. This study uses an integrated marketing communications (IMC). This research uses in-depth interview data collection techniques, observation and literature study in descriptive form. The results of this study are that Media Buffet uses an organic advertising strategy, direct marketing using the pitching method, interactive marketing that focuses on website and social media platforms managed by the internal digital marketing team, sales promotion through price cuts and bonuses, and uses public relations. In addition, as a complement to Media Buffet, it also uses an additional strategy, namely word of mouth.